The Effect Of Work Experience And Employee Placement at Bank Sulselbar Branch Majene: (Study on Employees of Bank Sulselbar Majene Branch) - Wahdaniah Wahdaniah; Nurul Listiawati; Nur Qomariah S; Awal Nopriyanto Bahasoan; Rizal Rizal (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to determine whether work experience and employee placement affect employee performance at PT. Bank Sulselbar Majene Branch. By using the SPSS version 25.0 method, there were 33 respondents who were used as samples in this study, namely employees of PT. Bank Sulselbar Majene Branch. The data collection technique uses a questionnaire and is distributed directly to the research sample. Analysis t test is used to test in this study. The results of this study indicate that (1) the work experience variable has a significant effect on employee performance (2) Employee Placement variable No has a significant effect on employee performance The results of this study indicate that work experience and employee placement have a simultaneous effect on employee performance at PT. Bank Sulselbar Majene Branch with a calculated F value of 69,006 is greater than the F table value of 3.32 with a significance of 0,000.